Targeted therapy Part I. Signalling by tyrosine kinase receptors - Wiczyńska, Beata; Rolski, Janusz (Contemporary Oncology/Współczesna Onkologia, 2007)
Cell signalling is tightly controlled for normal cell function. The signal transduction system comprises ligands (growth factors, cytokines, hormones), transmembrane receptors and cytoplasmic secondary messengers. The crucial effectors in signalling cascades include the Ras-Raf-MAP pathway, lipid kinase phosphoinositide-3-kinase (PI3K) pathway and protein kinase C pathway. Dysregulation of the three major signalling pathways can lead to the malignant phenotype of uncontrolled proliferation, metastasis, angiogenesis and inhibition of apoptosis.